Diversity in local cultivars of Pisum sativum collected from home gardens in Sweden. (October 2015) - Solberg, Svein Øivind; Brantestam, Agnese Kolodinska; Olsson, Kerstin; Leino, Matti Wiking; Weibull, Jens; Yndgaard, Flemming
Abstract: Although one would assume that finding any local cultivars in home gardens in a modern society such as Sweden is unlikely, such cultivars were in fact found. More than 170 seed accessions of vegetables, pulses and other seed-propagated garden crops maintained in home gardens and dating back at least to the 1950s have been assembled following the nationwide 'Seed Call'. Of these, 32 garden pea accessions were taxonomically characterized and compared with 43 accessions already present in the gene bank. In addition to morphological descriptors, SSR and retrotransposon-based iPBS markers were applied. Based on five SSR markers, potential duplicates could be located within nine pair/groups, or 25% of the accessions. Through combining this analysis with iPBS markers, the potential duplicates were reduced to five pair/groups. Combination of markers and the morphological descriptors further reduced the number to two groups; one group including four wrinkle-seeded accessions and one including two other wrinkle-seeded accessions. A combination of genotypic and phenotypic markers proved a good method to identify true and false duplicates. The results showed that the 'Seed Call' complements the NordGen collection and broadens the collection's genetic diversity. No clustering according to region of origin could be found, suggesting that the collected material predominantly represents old cultivars. Highlights: A collection mission has located 70 garden pea accessions dating to 1950 or earlier in Swedish home gardens. SSR markers, iPBS markers and PGene characterization showed that most accessions were unique. As very few accessions were shown to be duplicates, the new accessions complement the gene bank collection. No clustering according to region of origin could be found, suggesting that the material represents old cultivars.